The impact of environmental uncertainty on international joint venture performance: the mediating role of international joint venture adaptation. (2016) - Colak, Mustafa
This paper investigates the role of international joint venture (IJV) adaptation in the relationship between environmental uncertainty and IJV performance. Four hypotheses are developed concerning this relationship, predicting a direct positive relationship between uncertainty and adaptation (H1); a direct negative relationship between uncertainty and performance (H2); a direct positive relationship between adaptation and performance (H3); and a mediating effect of IJV adaptation on the relationship between uncertainty and IJV performance (H4). To test these hypotheses, path analysis, a special case of the structural equation modelling (SEM) technique, is used on questionnaire survey data from 102 manufacturing IJVs operating in Turkey. The results of this analysis were consistent with the first three hypotheses. The mediating effect of IJV adaptation (H4) was also confirmed by a Sobel test and the bootstrapping approach, suggesting that IJV adaptation mitigates the negative impact of environmental uncertainty on IJV performance.